INDONESIAN ROCK-PHOSPHATE EFFECTIVITY FOR MAIZE CROP ON ULTISOLS SOILS - Kasno, Antonius; Sutriadi, M.T. (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
Rock phosphate is a slow release phosphate source which can be directly used on acid soils. There are some rock phospahate deposits in Indonesia. Total phosphate and calcium content in rock phosphate vary between 8.79 â 31.88% P2O5, andÂ 0.60 â 57.50% Ca. The objective of these research is to study the Indonesian rock phosphate effectivity for maize on Ultisol soil. The research wasconducted at green house using randomized complete block design, 8 treatments and 5 replications. The treatments consist of 5 kinds of different Indonesian rock phosphate, control, supherphos fertilizer and Tunisia Rock Phosphate as a standard comparison of P fertilizer.Relative Agronomic Effectivenes Analyses was used to see the effectivity of eachÂ rock phosphate. The result of these study shows that the effectiveness of Rock Phosphate from Jampang Tengah Sukabumi (DE-1), Brati Kayen Pati (DE-9), Padaherang Ciamis (DE-3), and Karang Mulya Ciamis (DE-5) were aqually the same as Superphos. Indonesian Rock Phosphateâs effectivenesswas almost the same as Tunisian Rock Phosphate. Phosphate fertilizing using rock phosphate obviously increased the soil content of phosphorus, both the available P and the reserved ones, and Superphos did better than the rock phosphate. Rock phosphate effectivity on Typic Plintudults was lower than thaton Typickanhapludults. Â Keywords: Â Â rock phosphate, effectivity, typicplin-thudults, typickanhapludults, maize